PENGGUNAAN GAYA BAHASA EUFEMISME PADA PERNYATAAN RESMI PRESIDEN JOKOWI PERIODE 2014-2019 - Kasri Riswadi (JURNAL ILMU BUDAYA, 2021)
This research is based on the use of the euphemism style by President Jokowi as head of state. The purpose of this study is (1) to describe the establishment of the euphemism language style used in President Jokowi's official statement for the period 2014-2019 and (2) to explain the reasons for the use of euphemism style in President Jokowi's official statement. The type of research used is qualitative descriptive language research. The results showed that President Jokowi used a style of euphemism in his official statement in the period 2014-2019. The formation of euphemism style is carried out in the form of figurative expression, flippancy, circumlocution, and hyperbole. The reason for President Jokowi's use of euphemisms is for the function of protecting oneself, presenting imagery, insinuating or subtly criticizing, avoiding panic, and the desire to retain power.